Balancing Personal and Professional Life: A Study of Experiences and Perceptions of Divorced People - Bhandari, Mohan; Tiwari , Ghanashyam (Prithvi Academic Journal, 2024)
This study intends to evaluate the emotional and psychological aspects of divorce, with a special emphasis on the delicate interplay between their personal and professional lives. Purposive sampling was utilized in conjunction with semi-structured interviews under the constructivist-interpretive technique. During the interviews, all procedures were carried out with the participants' informed consent with strong ethical norms to protect confidentiality. Member verification and consistent data analysis were used to maintain credibility. The data obtained from the interview were thematically analyzed to detect reoccurring patterns throughout the narratives. The study found that gender and culture have an impact on individual experiences, but mindfulness, meditation, and therapy are essential for overcoming the emotional difficulties associated with divorce. Personalized coping strategies, encouraging workplaces, therapeutic interventions, and a more thorough comprehension of gender and culture-specific variables are essential. These findings have significant implications for therapists assisting, businesses developing compassionate workplaces, governments concerned about the emotional well-being of their constituents, and divorcees seeking support. The study investigates the firsthand encounters of individuals managing the balance between work and professional life amidst divorce, providing crucial perspectives for practitioners assisting individuals and similar circumstances.